Pengeluaran Wajib Anggaran Pendidikan dan Kesehatan di Papua - Boy Piter Nizu Kekry (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
This study aims to reveal the phenomenon of compliance with mandatory spending on education and health in 29 regencies/cities in Papua. The data analysis method applies quantitative descriptive data by using regional financial data, namely: Regional Revenue and Expenditure Targets, Education and Health Expenditure Allocation for Fiscal Year 2021, Realization of Regional Income, and Expenditure, Education and Health Expenditure Allocation for the Fiscal Year 2017-2020. The main finding of this study is that 27 local governments have not complied with mandatory spending on education, while for health, there are six local governments in Papua. Of course, this fact indicates one of the weaknesses in achieving the competitiveness of human development in Papua. Next is the fact that study results show that the amount of regional income and expenditure is not necessarily accompanied by the level of compliance with mandatory spending. This indicates the poor quality of planning and budgeting at the local government level in Papua. The author is aware of the limitations of this study; in disclosing the facts of compliance with mandatory spending on education and health, it is hoped that further research can measure the impact of mandatory spending on regional development performance indicators through an econometric model approach.